Temperature- and pH-dependent aggregation behavior of hydrophilic dual-sensitive poly(2-oxazoline)s block copolymers as latent amphiphilic macromolecules. (March 2017) - Zschoche, Stefan; Rueda, Juan Carlos; Binner, Marcus; Komber, Hartmut; Janke, Andreas; Appelhans, Dietmar; Voit, Brigitte
Graphical abstract: Highlights: Double hydrophilic poly(2-oxazoline)s block copolymers usable as amphiphilic macromolecules. Latent amphiphilic macromolecules fabricated by simultaneous pH and temperature stimulus. Most amphiphilic macromolecules preferentially form vesicles in aqueous solution. Membrane thickness of vesicles correlates with the organization of the block copolymers in vesicles' membrane. Abstract: A variety of hydrophilic diblock and triblock copolymers of AB and ABA type with temperature-sensitive poly(2-isopropyl-2-oxazoline) blocks und pH-sensitive poly(2-carboxyethyl-2-oxazoline) blocks have been synthesized. The temperature- and pH-induced reversible phase transition renders the block copolymers as amphiphilic macromolecules and allows for defined aggregation through self-assembly following the packing parameter of amphiphilic macromolecules. Size, structure and arrangement of the individual block copolymer segments define the temperature and pH values of the transitions as well as the nature of the formed aggregates. DLS measurements were used to determine the transition temperatures at selected pH values in aqueous solution whereas AFM was used to visualize and characterize the formed aggregates adsorbed on Si wafer surfaces. In the case of vesicles formed by the diblock and triblock copolymers, double and monolayer membranes could be verified. The tendency of different states of organization of poly(2-isopropyl-2-oxazoline) blocks from crystalline to amorphous is assumed to be the cause for the different box-like structures determined on Si wafer surfaces.